Building vertically-structured, high-performance electrodes by interlayer-confined reactions in accordion-like, chemically expanded graphite. (April 2020) - Dong, Lei; Zhang, Long; Lin, Shan; Chen, Zhongxin; Wang, Yannan; Zhao, Xiaoxu; Wu, Tianqi; Zhang, Jiajia; Liu, Wei; Lu, Hongbin; Loh, Kian Ping
Abstract: Graphene has attracted major interests as electrode materials for energy storage applications. However, the major limitation of using blade- or spin-coated graphene films for fabricating electrode is that the basal plane of the flat-lying graphene is orthogonal to the direction of charge transport, causing sluggish charge transfer kinetics for the coated graphene film. Here we propose a general, scalable strategy to prepare vertically-structured hybrid electrodes using accordion-like, chemically expanded graphite (CEG). The coated CEG rods possess two-dimensional (2D) interlayer galleries that are vertically aligned with respect to the substrate because of their large length-diameter ratio, which facilitates high-efficiency ion transport. Due to its excellent wettability and high electrochemical surface areas, these interlayer galleries allow a high loading of redox-active (RA) materials, including metal (Pt), metal hydroxide (Ni(OH)2, Fe2 O3 and MnO2 ) or metal dichalcogenide (MoS2 ). As an example, Ni(OH)2 -infiltrated CEG shows excellent rate-performance and long-term cycling stability when used as electrochemical electrodes in lithium-ion batteries and supercapacitors. Graphical abstract: Vertically-structured hybrid electrodes with fast charge transfer kinetics are fabricated via a general, scalable strategy. By understanding the intrinsic, vertically-oriented ion transport channels in chemically expanded graphite (CEG), various hybrid electrodes are synthesized by an interlayer-confined reaction. As an example, Ni(OH)2 -infiltrated CEG electrodes exhibit excellent electrochemical performances for the lithium-ion battery and supercapacitor applications. Image 1 Highlights: A general, scalable strategy to prepare vertically-structured electrodes using chemically expanded graphite. Wide applicability in fabricating a variety of hybrid electrodes. Improved ion-transport kinetics. Superior performances when used as electrodes in both lithium ion batteries and supercapacitors.